Henry Aaron Hill papers - Hill, Henry Aaron, 1915-1979.
Correspondence, memoranda, minutes, notes, reports, scientific papers, transcripts, writings, academic records, family papers, financial and business records, newspaper clippings, blueprints, plans, map, memorabilia, printed matter, and photographs documenting Hill's career in the chemical industry, activities in related organizations, service on governmental and educational advisory boards, and his personal and family life. Includes material on his years as a student at Johnson C. Smith University and Massachusetts Institute of Technology and later as an advisor to both institutions; his career as an organic chemist, authority on polymer chemistry and inflammable textiles, and founder and president of Riverside Research Laboratory, Haverhill, Mass., and its affiliate, Sigma Chemical Company; his association with the American Chemical Society as a member of various committees and as its first African American president; membership on the National Commission on Product Safety, National Motor Vehicle Safety Advisory Council, and advisory council to the U.S. Senate Commerce Committee Consumer Subcommittee; his research interest in synthetic rubber, rubber additives, synthesis of polymers, polyvinyl chloride, fluorine chemistry, foam rubber, and plastics. Persons represented include his brother, ceramic artist William Anthony (Tony) Hill, his son, Anthony Cromwell Hill, and Edward William Brooke.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Chemist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brooke, Edward W. -- 1919-; Hill, Anthony Cromwell; Hill, William Anthony, -- 1907-1975.; American Chemical Society; Johnson C. Smith University; Massachusetts Institute of Technology; Riverside Research Laboratory (Haverhill, Mass.); Sigma Chemical Company; United States. -- Congress. -- Senate. -- Committee on Commerce. Consumer Subcommittee; United States. -- National Commission on Product Safety; United States. -- National Motor Vehicle Safety Advisory Council; African American chemists; Chemical industry; Chemical laboratories -- Massachusetts -- Haverhill; Chemistry, Organic; Fireproofing of fabrics; Fluorine; Foam rubber; Inflammable fabrics; Plastics; Polymers; Polyvinyl chloride; Product safety; Rubber -- Additives; Rubber, Artificial; Traffic safety; Chemists